1994
DOI: 10.1111/j.1574-6976.1994.tb00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbes in food processing technology

Abstract: There is an increasing understanding that the microbial quality of a certain food is the result of a chain of events. It is clear that the microbial safety of food can only be guaranteed when the overall processing, including the production of raw materials, distribution and handling by the consumer are taken into consideration. Therefore, the microbiological quality assurance of foods is not only a matter of control, but also of a careful design of the total process chain. Food industry has now generally adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Based on the C T values found in the samples containing serotype Enteritidis under our experimental conditions, the concentration of the microorganism in the preenrichment culture after 18 to 20 h of incubation at 37°C was always greater than 10 8 CFU/ml. This result suggests that the incubation period of the preenrichment medium can be reduced, thus shortening the time required for this method while maintaining its effectiveness and rendering it particularly useful for determining the effectiveness of the hazard analysis and critical point systems used in the food industry to reduce the numbers of pathogenic germs (12).…”
Section: Discussionmentioning
confidence: 98%
“…Based on the C T values found in the samples containing serotype Enteritidis under our experimental conditions, the concentration of the microorganism in the preenrichment culture after 18 to 20 h of incubation at 37°C was always greater than 10 8 CFU/ml. This result suggests that the incubation period of the preenrichment medium can be reduced, thus shortening the time required for this method while maintaining its effectiveness and rendering it particularly useful for determining the effectiveness of the hazard analysis and critical point systems used in the food industry to reduce the numbers of pathogenic germs (12).…”
Section: Discussionmentioning
confidence: 98%
“…With the availability of the polymerase chain reaction (PCR) it has become possible to detect specific bacteria with high speed and sensitivity (Hofstra et al 1994). Since the DNA sequences of some genes are highly conserved, PCR can also be applied to detect specific genes in various organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in evaluating the level of microbial contamination in places at risk has increased and is considered to be an essential step toward infection prevention. 1,2 Recent epidemiological studies have reported fomites in the transmission of human pathogens within high-exposure environments such as hospitals, child-care facilities, long-term care facilities, and sports facilities. 3,4 Various types of microorganisms were identified, including rotavirus, rhinovirus, methicillin-resistant Staphylococcus aureus (MRSA), and Serratia marcescens, to cause gastrointestinal diseases, the common cold, necrotizing fasciitis, and catheter associated bacteremia, respectively.…”
Section: Introductionmentioning
confidence: 99%